PENGARUH APLIKASI SISTEM INFORMASI SIGILIB TERHADAP PENINGKATAN KINERJA PUSTAKAWAN DI PERPUSTAKAAN ISI SURAKARTA - Mustofa Mustofa (JURNAL ILMU PERPUSTAKAAN (JIPER), 2021)
The purpose of this study was to determine the extent of the influence of the application of the information system "SIGILIB" on the improvement of librarian performance at the UPT Library of ISI Surakarta. This research is descriptive quantitative in nature with research subjects are all librarians of the ISI Surakarta library, totaling 12 people. The object of this research is the SIGILIB Information System Application. Based on the results of data analysis from research that: 1) the main average of the SIGILIB Information System Application variable is 3,818. This value is on a scale range of 3.40 - 4.20 which indicates that it is at a high level. 2) The Grand Mean of the Performance variable carried out by the librarian is 4.175. This value is in the scale range from 3.40 to 4.20 which indicates that the performance of librarians at the ISI Surakarta library is at a high level. Relationship between SIGILIB Information System and Librarian Performance has a very strong relationship, the nature of the relationship between SIGILIB Information System and Librarian Performance. Because the value found the influence of the SIGILIB Information System on Librarian Performance is 0.898, the value is between 0.80 - 1,000. The data processing results show that the SIGILIB Information System variable t-count is greater than the t-table (6,456> 2,228) with a probability (0,000) less than the significant level of 0.05, thus Ho is rejected and Ha is accepted, meaning that there is a significant effect. between the SIGILIB Information System veriabel on the performance of librarians at the Indonesian Institute of the Arts, Surakarta.